High School Football and Risk for Depression and Suicidality in Adulthood: Findings From a National Longitudinal Study - Iverson, Grant L.; Terry, Douglas P. (Frontiers in Neurology, 2022)
Background: There is growing public concern regarding the potential long-term effects of playing football on brain health, specifically that playing football before and during high school might cause damage to the brain that manifests years or decades later as depression or suicidality. This study examined if playing high school football was associated with increased lifetime risk for depression, suicidality over the past year, or depressed mood in the past week in men aged between their middle 30s to early 40s. Methods: Publicly available data from the National Longitudinal Study of Adolescent to Adult Health were analyzed. This longitudinal, prospective cohort study sampled nationally representative U.S. youth starting in 1994-1995 (Wave I) and most recently in 2016-2018 (Wave V). A total of 3,147 boys participated in Wave I (median age=15), of whom 1,805 were re-assessed during Wave V (median age=38). Results: Of the 1,762 men included in the study, 307 (17.4%) men reported being diagnosed with depression and 275 (15.6%) reported being diagnosed with an anxiety disorder or panic disorder at some point in their life. When comparing men who played high school football to those who did not, there were no differences in the proportions of the sample who had a lifetime diagnosis of depression, lifetime diagnosis of anxiety/panic disorders, suicidal ideation in the past year, psychological counseling in the past year, or current depressed mood. However, men who received psychological counseling and/or experienced suicidal ideation during adolescence were significantly more likely to report a lifetime history of depression, suicidal ideation in the past year, and current depressed mood. Conclusion: Individuals who reported playing football during adolescence did not have an increased risk of depression or suicidal ideation when they were in their middle 30s to early 40s, but mental health problems during adolescence were associated with an increased risk for psychological health difficulties more than 20 years later.